2021
DOI: 10.1371/journal.pone.0256402
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of burnout among university students in low- and middle-income countries: A systematic review and meta-analysis

Abstract: Background Burnout is common among university students and may adversely affect academic performance. Little is known about the true burden of this preventable malady among university students in low-and-middle-income countries (LMICs). Objectives This study aimed to systematically estimate the prevalence of burnout among university students in LMICs. Methods We searched PubMed, Google Scholar, CINAHL, Web of Science, African Journals Online, and Embase from the inception of each database until February 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 70 publications
0
34
0
1
Order By: Relevance
“… 11 Moreover, burnout prevalence was reported to be lower among university students in low- and middle-income countries during the COVID-19 pandemic as compared to the burnout prevalence observed before the COVID-19 pandemic. 13 …”
Section: Introductionmentioning
confidence: 99%
“… 11 Moreover, burnout prevalence was reported to be lower among university students in low- and middle-income countries during the COVID-19 pandemic as compared to the burnout prevalence observed before the COVID-19 pandemic. 13 …”
Section: Introductionmentioning
confidence: 99%
“…A worldwide meta-analysis showed that the global prevalence of burnout among university students was 12.1%, which was double the prevalence reported in this article 17 . In addition, studies conducted in the Arabian region showed that the prevalence of burnout ranged between 19% in Syria 18 and 80% in Egypt 19 and both were higher than the prevalence we reported in this article.…”
Section: Discussionmentioning
confidence: 42%
“…Challenges in the higher education context make students also susceptible to symptoms of burnout (cf. Hobfoll, 1989 ; Kaggwa et al., 2021 ). Salmela-Aro et al.…”
Section: Literature Reviewmentioning
confidence: 99%